Enhanced thermal conductivity of epoxy composites filled with silicon carbide nanowires - Dianyu Shen (Nature Portfolio, 2017)
Abstract In this study, we report a facile approach to fabricate epoxy composite incorporated with silicon carbide nanowires (SiC NWs). The thermal conductivity of epoxy/SiC NWs composites was thoroughly investigated. The thermal conductivity of epoxy/SiC NWs composites with 3.0 wt% filler reached 0.449 Wm−1 K−1, approximately a 106% enhancement as compared to neat epoxy. In contrast, the same mass fraction of silicon carbide micron particles (SiC MPs) incorporated into epoxy matrix showed less improvement on thermal conduction properties. This is attributed to the formation of effective heat conduction pathways among SiC NWs as well as a strong interaction between the nanowires and epoxy matrix. In addition, the thermal properties of epoxy/SiC NWs composites were also improved. These results demonstrate that we developed a novel approach to enhance the thermal conductivity of the polymer composites which meet the requirement for the rapid development of the electronic devices.